2019
DOI: 10.1051/metal/2019041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alkali metal on solution loss and coke degradation

Abstract: To research the effect of alkali metals on the solution-loss rate and coke strength after reaction, potassium and sodium vapors were prepared by a high-temperature thermal-reduction method, and the thermal properties of four industrial cokes that absorbed potassium and sodium vapor were studied. The thermal properties include the traditional thermal-property indices, coke reactive index and coke strength after reaction, and the coke strength after a 25% mass loss, which is obtained by a continuous thermogravim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The results indicated that the reactivity of coke gradually increased and the strength of coke gradually deteriorated with as the alkali compound content increased after gasification under different temperatures. Zhao et al 23 and Yu et al 24 found that both K and Na vapors might promote the gasification and dissolution reaction of coke; however, the catalytic effect of K on the gasification and dissolution reaction of coke was stronger than that of Na. The above investigations showed that alkali compounds might deteriorate the quality of coke, but few studies have been conducted on the variability of the radial dissolving loss of coke particles during alkali-rich coke gasification reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the reactivity of coke gradually increased and the strength of coke gradually deteriorated with as the alkali compound content increased after gasification under different temperatures. Zhao et al 23 and Yu et al 24 found that both K and Na vapors might promote the gasification and dissolution reaction of coke; however, the catalytic effect of K on the gasification and dissolution reaction of coke was stronger than that of Na. The above investigations showed that alkali compounds might deteriorate the quality of coke, but few studies have been conducted on the variability of the radial dissolving loss of coke particles during alkali-rich coke gasification reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the reactivity of coke gradually increased and the strength of coke gradually deteriorated with as the alkali compound content increased after gasification under different temperatures. Zhao et al 23 and Yu et al 24 found that both K and Na vapors might promote the gasification and dissolution reaction of coke; however, the catalytic effect of K on the gasification and dissolution reaction of coke was stronger than that of Na.…”
Section: Introductionmentioning
confidence: 99%